The Role of Price in the International Trade Mechanism - Carr, Robert M. (Quarterly Journal of Economics, 1931)
Journal Article The Rôle of Price in the International Trade Mechanism Get access Robert M. Carr Robert M. Carr University of California Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 45, Issue 4, August 1931, Pages 710–719, https://doi.org/10.2307/1883251 Published: 01 August 1931